An after-school intervention targeting executive function and visuospatial skills also improves classroom behavior. (September 2018) - Brock, Laura L.; Murrah, William M.; Cottone, Elizabeth A.; Mashburn, Andrew J.; Grissmer, David W.
Executive function (EF) describes a complex set of skills, including flexible attention, inhibitory control, and working memory, that coordinate to achieve behavioral regulation. Visuospatial skills (VS) describe the capacity to visually perceive and understand spatial relationships among objects. Emerging research suggests VS skills are associated with classroom functioning, including behavioral adjustment. Children from socioeconomically disadvantaged backgrounds are more likely to enter school with EF and VS deficits, with consequences for classroom adjustment. In response, we developed and experimentally tested an after-school intervention that incorporates fine and gross motor activities targeting EF and VS skills in a sample of 87 kindergarten and first-grade students from low-income communities. The aim of the present study was to preliminarily explore whether EF and VS skills were bolstered by the intervention and subsequently whether EF and VS skills mediate or moderate intervention impacts on learning-related and problem behaviors in the classroom. Intent-to-treat analyses confirm intervention effects for EF and VS skills. Using full information maximum likelihood and bias-corrected bootstrapping, results indicate that improvements in EF mediated the impact of assignment to the treatment condition on improvements in learning-related behaviors and reductions in problem behavior. Taken together, findings suggest out-of-school contexts are a reasonable point of intervention for improving daytime classroom behavior.